A Biomechanical Evaluation of Three Drop Wire Configurations. Issue 6 (24th June 2013) - Arango, Johnattan; Lewis, Daniel D.; Hudson, Caleb C.; Horodyski, MaryBeth
Abstract Objective Evaluate effect of adding drop wires to single‐ring constructs. Study Design Biomechanical study Sample Population Single ring circular external skeletal fixator constructs stabilizing a Delrin segment bone model. Methods Eight replicates of 5 constructs made with 66 mm complete rings, 1.6 mm olive wires, and a 15.9‐mm diameter Delrin rod were loaded in axial compression, craniocaudal and mediolateral bending, and torsion. Constructs tested were: (1) base single‐ring construct; (2) single‐ring construct with a drop wire mounted on fixation bolts; (3) single‐ring construct with a drop wire mounted on 1‐hole posts; (4) single‐ring construct with a drop wire mounted on 2‐hole posts; and (5) 2‐ring construct. Construct stiffness for each mode of loading was compared using repeated measures ANOVAs (P ≤ .05). Results Axial compression and torsion: the 2‐ring construct was stiffer than all others. Drop wire constructs were stiffer than the single‐ring construct, but not significantly different from each other. Craniocaudal bending: the 2‐ring construct was stiffest with the 2‐hole post construct being stiffer than all except the 2‐ring construct. Mediolateral bending: the 2‐hole post construct was stiffer than the 2‐ring construct, which was stiffer than the 1‐hole post construct, which was stiffer than the fixation‐bolt construct, which was stiffer than the single‐ring construct. Conclusions Drop wires improved stiffness of single‐ring constructs in all loading modalities. Positioning the drop wire farther from the ring surface significantly improved craniocaudal and mediolateral bending stiffness, but did not affect axial compression and torsional stiffness.